2021
DOI: 10.1111/codi.15521
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of stool DNA methylation tests in colorectal cancer screening: a systematic review and meta‐analysis

Abstract: Aim There is not sufficient evidence about whether stool DNA methylation tests allow prioritizing patients to colonoscopy. Due to the COVID‐19 pandemic, there will be a wait‐list for rescheduling colonoscopies once the mitigation is lifted. The aim of this meta‐analysis was to evaluate the accuracy of stool DNA methylation tests in detecting colorectal cancer. Methods The PubMed, Cochrane Library and MEDLINE via Ovid were searched. Studies reporting the accuracy (Sackett phase 2 or 3) of stool DNA methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Because no cancers were observed ≤5 years after previous negative screening colonoscopy, and the rates of advanced adenoma ≤5 years were the same as seen 6–9 years after colonoscopy, we propose that mt-sDNA be studied in the future as an interval screening test 5 years after negative screening colonoscopy with or without comparison to FIT. Although not yet available in the United States, there are other methylated stool-based tests in development ( 42 ) and in commercial use ( 43 , 44 ). Although these tests will require validation and approval in the United States, prospective comparison between the stool-based tests with concurrent colonoscopy will be invaluable for assessing differences in test performance and potential use as an adjunct to colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Because no cancers were observed ≤5 years after previous negative screening colonoscopy, and the rates of advanced adenoma ≤5 years were the same as seen 6–9 years after colonoscopy, we propose that mt-sDNA be studied in the future as an interval screening test 5 years after negative screening colonoscopy with or without comparison to FIT. Although not yet available in the United States, there are other methylated stool-based tests in development ( 42 ) and in commercial use ( 43 , 44 ). Although these tests will require validation and approval in the United States, prospective comparison between the stool-based tests with concurrent colonoscopy will be invaluable for assessing differences in test performance and potential use as an adjunct to colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several meta-analyses assessing the diagnostic value of stool DNA testing [ 343 , 344 , 345 , 346 , 347 , 348 ]. Zhai et al reported the pooled sensitivities for single- and multiple-gene stool DNA (methylation and mutation) tests in CRC to be 48.0% and 77.8%, respectively, and the pooled specificity for single- and multiple-gene assays to be 97.0% and 92.7%, respectively [ 344 ].…”
Section: Diagnostic Stool Biomarkers For Colorectal Cancermentioning
confidence: 99%
“…In Mojtabanezhads et al‘s meta-analysis, this method was shown to have a lower efficiency than reported in previous meta-analyses: the sensitivity for CRC and adenomas was 56.5% and 32.6%, respectively, and the specificity was 93.2% for CRC and adenomas [ 347 ]. In a published meta-analysis including results obtained for over 16,000 patients, it was revealed that the sensitivity of the stool methylation test with a single SDC2 gene was 83.1% and specificity was 91.2%, what is promising in case of this diagnostic method as employed instead of colonoscopy [ 348 ].…”
Section: Diagnostic Stool Biomarkers For Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous meta-analyses [ 36 ] and systematic reviews [ 37 ] have analyzed and evaluated SDC2 methylation derived from feces and blood, respectively, for colorectal cancer screening, they included a small number of articles and lacked specific study analysis of SDC2 methylation. Our study was the first meta-analysis to investigate the performance of SDC2 methylation for colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%